2022
DOI: 10.4254/wjh.v14.i7.1382
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome changes in stages of non-alcoholic fatty liver disease

Abstract: BACKGROUND Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the United States and globally. The currently understood model of pathogenesis consists of a ‘multiple hit’ hypothesis in which environmental and genetic factors contribute to hepatic inflammation and injury. AIM To examine the genetic expression of NAFLD and non-alcoholic steatohepatitis (NASH) tissue samples to identify common pathways that contribute to NAFLD and NASH pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Compared to normal (<5% steatosis) livers, they noted upregulation in FABP5 along with other genes involved in lipogenesis. [ 38 ] Other studies [ 39,40 ] have also shown a strong correlation between fat accumulation in the liver and the upregulation of FABP5, ACSL4, and ACACA. The observation of a similar increase in these factors in primary human hepatocytes suggests that excess fat remaining on ECM collected from highly steatotic livers may lead to a NAFLD‐like phenotype in liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normal (<5% steatosis) livers, they noted upregulation in FABP5 along with other genes involved in lipogenesis. [ 38 ] Other studies [ 39,40 ] have also shown a strong correlation between fat accumulation in the liver and the upregulation of FABP5, ACSL4, and ACACA. The observation of a similar increase in these factors in primary human hepatocytes suggests that excess fat remaining on ECM collected from highly steatotic livers may lead to a NAFLD‐like phenotype in liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…The higher glycemia observed in the group of patients with severe NAFLD probably evidences a worsening of insulin resistance at this stage of the disease. The metabolic pathways involved in NAFLD progression are not well characterized, but low-grade chronic inflammation and oxidative stress take part in the pathogenesis and progression of NAFLD [ 46 , 47 ]. MDA, the PUFA peroxidation marker of oxidative stress [ 48 ], is progressively increased with the stage of NAFLD, and its plasma levels are significantly correlated with the IFC, reflecting that low-grade oxidative stress is secondary to the accumulation of fatty acids in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Intrahepatic lipid saturation predisposes the liver to inflammation; however, the mechanisms by which this intrahepatic lipid saturation promotes NAFLD progression are still poorly understood [ 46 ]. The obtained data show that the plasma levels of 12HEST and 17HDoHE are the lipid mediators with the highest correlation with the intrahepatic fat content in NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that PI3K/AKT signaling is significantly upregulated in patients with nonalcoholic fatty liver disease, one of the risk factors for AS, and inhibitors against PI3K and AKT have potential regulatory effects on lipid metabolism (Aljabban et al. 2022 ). Our results showed that phosphorylation of the PI3K/AKT signaling pathway in the liver of AS model mice is significantly activated, resulting in elevated SREBPs.…”
Section: Discussionmentioning
confidence: 99%